Finite-element modelling of seismoelectric and electroseismic waves in frequency domain: 2-D SHTE mode - Wang, Dongdong (2023)
We propose a frequency-domain finite-element (FDFE) method to simulate the 2-D SHTE mode seismoelectric and electroseismic waves. By neglecting the secondary weak wavefield feedbacks, the SH and TE waves are solved, separately. In a finite plane region, propagations of both SH and TE waves can be described as the Helmholtz equation with boundary conditions, which is proved to be equivalent to the extremum of functional by conducting calculus of variation. The computation region is partitioned into structured rectangular elements with the bilinear interpolation. The proposed FDFE algorithm solves the wavefield in frequency domain and avoids adopting the quasi-static approximation. One advantage of the proposed algorithm is its ability to accurately simulate the seismoelectric and electroseismic responses generated from the free surface. We verify the proposed algorithm based on a layered model beneath a free surface by comparing the waveforms calculated using the FDFE algorithm with those calculated using analytically-based method. The proposed algorithm is applied in feasibility studies of interface seismoelectric and electroseismic responses in exploring the hydrocarbon reservoir and monitoring the time-lapse pollutant within a sand channel.